PENGARUH LITERASI KEUANGAN, USIA, DAN BIMBINGAN ORANG TUA TERHADAP PENGELOLAAN UANG SAKU MAHASISWA UNINDRA - Rendika Vhalery; Ari Wahyu Leksono; Moh. Irvan (Jurnal Pendidikan Ekonomi, 2019)
The aim of this research to find the impact from financial literature, age, and parental guidance toward provision money. The type of this research is associative quantitative with using population amount which are 1229 students and 273 students from UNINDRA. Data gathering technique uses questionnaires that are already tested with viability and reliability test. Analysis technique uses double linear regression technique with SPSS 24.0 for windows operation system. The result shows 1) financial literature affects provision money management significantly, 2) age does not significantly affect the provision money management, 3) parental guidance does not affect the provision management, and 4) financial literature, age, and parental guidance affect the provision management significantly.